PENGARUH PROMOSI, HARGA DAN KUALITAS PELAYANAN TERHADAP MINAT BELI KONSUMEN DI BAKSO TERMINAL 1974 LAREN LAMONGAN - Nurul Ain; Nawari Nawari (Pro-fit, 2023)
This study was conducted to determine the effect of promotion, price and service quality on consumer buying interest at Bakso Terminal 1974 Laren Lamongan by using quantitative methods of primary data. The results show that promotion has an effect on consumer buying interest with tcount = 2.873 > ttable = 1.988, price has no effect on consumer buying interest with tcount = 1.916 < ttable = 1.988 and service quality affects consumer buying interest tcount = 7,413 > ttable = 1.988. Simultaneous F-test shows that promotion, price and service quality affect consumer buying interest with Fcount = 453.767 > Ftable = 2.70 with a coefficient of determination of 93.4%.